2023
DOI: 10.2147/jir.s401444
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Serum Heat Shock Protein 90α on the Prognosis of Patients with Lung Adenocarcinoma

Abstract: Purpose Heat shock protein 90α (HSP90α) is highly expressed in tumors, and predicts tumor progression. This study analyzed the correlation between the expression level of HSP90α in the serum and the prognosis of patients with lung adenocarcinoma. Patients and methods The medical records of patients with 228 lung adenocarcinoma from September 2015 to December 2021 were analyzed. HSP90α expression in the patients’ serum was detected by ELISA and the cut-off value (93.76 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, HSP90α expression was higher in lung cancer patients’ serum in comparison to healthy individuals’ serum, indicating that HSP90 could be employed as a novel biomarker for the diagnosis of lung cancer [ 225 ]. A recent study by Fang et al found that HSP90α expressions were positively correlated with tumor–node–metastasis staging in patients with lung adenocarcinoma and suggested combining HSP90α with carcinoembryonic antigen for more effective prediction of patient prognosis [ 226 ]. The growing evidence that shows a link between HSP expression and lung cancer differentiation and staging suggests that HSPs can be used as a potential biomarker and therapeutic target to treat lung cancer.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%
“…Moreover, HSP90α expression was higher in lung cancer patients’ serum in comparison to healthy individuals’ serum, indicating that HSP90 could be employed as a novel biomarker for the diagnosis of lung cancer [ 225 ]. A recent study by Fang et al found that HSP90α expressions were positively correlated with tumor–node–metastasis staging in patients with lung adenocarcinoma and suggested combining HSP90α with carcinoembryonic antigen for more effective prediction of patient prognosis [ 226 ]. The growing evidence that shows a link between HSP expression and lung cancer differentiation and staging suggests that HSPs can be used as a potential biomarker and therapeutic target to treat lung cancer.…”
Section: Biomarkers and Their Biosensorsmentioning
confidence: 99%